Methodological notes on analyzing the manufactured export performance in less developed countries - William G. Tyler (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1973)
Import substituting industrialization has increasingly come under criticism as a strategy for economic growth in the less developed countries. Many economists, in both the developed and less developed countries, have become highly skeptical of the benefits of inward looking development and have advocated outward looking growth, emphasizing the export of manufactures, as a viable growth strategy. In analyzing the manufactured export performance of the less developed countries, a number of methodological questions are raised. This paper, originally prepared as three separate notes, focuses on some usable methodological tools for the economic analyst. Chapter I provides a discussion of some of the econometric problems involved in quantitatively estimating the determinants of manufactured export behavior in less developed countries. An ordinary least squares regression model for analyzing manufactured export behavior in the relatively short run is developed and discussed. In Chapter II neo-classical microeconomic theory is adapted to the problem of analyzing export behavior of the industrial firm in a less developed economy. Under the assumptions of profit maximizing behavior and economically separate domestic and foreign markets, a micro model of export behavior is developed subject to the constraint of the firm's production function. Chapter III presents a methodology for measuring the demand side contribution of import substitution and export expansion as ex post explanations of industrial growth. An alternative, more comprehensive approach to the traditional Chenery and recent Morley-Smith approaches to measurement is developed.
Keywords: 330